Multicolour photochromism of colloidal solutions of niobate nanosheets intercalated with several kinds of metal ions. Issue 16 (29th January 2016) - Kamada, Kai; Tanaka, Yosuke; Tokunaga, Motoko; Ueda, Taro; Hyodo, Takeo; Shimizu, Yasuhiro
Abstract : Niobate nanosheets show multicolour photochromism depending on the kind of coexisting metal ions. Abstract : Colourless and transparent colloidal solutions of niobate nanosheets intercalated with some kinds of metal ions (M-NNS, M: metal) showed quasi-reversible photochromism. Ultraviolet light irradiation of the solutions induced a change in color while maintaining the transparency, and the color change was dependent on the metal ions. The coloured solutions were bleached by exposure to an oxidizing atmosphere. This cycle could be repeated several times.